Laparoscopic approach for hospitalized women in reproductive period presenting with non-specific abdominal pain - Cikot, Murat; Binboga, Sinan; Akarsu, Cevher; Surek, Ahmet; Gemici, Eyup; Alper Sahbaz, Nuri; Kartal, Bahadir; Alis, Halil (Annals of Medical Research, 2021)
None
Keywords: Nonspecific Abdominal Pain; Women; Reproductive Period; Laparoscopy.